2019
DOI: 10.1007/s11682-019-00083-x
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of cognitive control deficits in children with reading disorder

Abstract: Reading disorder (RD) is characterized by deficient phonological processing, but children with RD also have cognitive control deficits, the neural correlates of which are not fully understood. We used fMRI to assess neural activity during the resolution of cognitive conflict on the Simon Spatial Incompatibility task and patterns of resting-state functional connectivity (RSFC) from task control (TC) regions in 7-12-year-old children with RD compared to their typically developing (TD) peers. Relative to TD child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 57 publications
1
13
1
Order By: Relevance
“…Like prior findings, we observed an inverse association between age and FP-DMN network connectivity ( Chai et al, 2014 ). However, in contrast to prior findings ( Margolis et al, 2019 ; Koyama et al, 2013 ), we observed near-zero, rather than positive connectivity values in the youngest age group. Specifically, our findings indicate that youth in early childhood demonstrate highly variable connectivity that averages to near-zero between some regions in the DMN and FP (frontomedial cortex-IFG, precuneus-IFG, frontal pole – precentral gyrus) while other regions show early anticorrelations (frontal pole – IFG).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Like prior findings, we observed an inverse association between age and FP-DMN network connectivity ( Chai et al, 2014 ). However, in contrast to prior findings ( Margolis et al, 2019 ; Koyama et al, 2013 ), we observed near-zero, rather than positive connectivity values in the youngest age group. Specifically, our findings indicate that youth in early childhood demonstrate highly variable connectivity that averages to near-zero between some regions in the DMN and FP (frontomedial cortex-IFG, precuneus-IFG, frontal pole – precentral gyrus) while other regions show early anticorrelations (frontal pole – IFG).…”
Section: Discussioncontrasting
confidence: 99%
“…As we were specifically interested in how FP-DMN connectivity might become more anticorrelated (negative) with age, we used aCompCor to regress out signal from white matter and cerebrospinal fluid. Two of the prior studies that reported positive FP-DMN findings in young children used aCompCor ( Margolis et al, 2019 ; Chai et al, 2014 ). One used global signal regression ( Koyama et al, 2013 ) but nevertheless still reported positive FP-DMN connectivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These specific regions are located in the frontal-parietal cognitive/attention network (involved in many cognitive tasks, cognitive control, learning and planning, etc.) (Margolis et al, 2019). Based on resting-state functional connectivity and graph theory analysis, a two-system model for cognitive control, including FPN and the cingulo-opercular network, is proposed as the commanders of the brain (Cignetti et al, 2018).…”
Section: Interactive Neural Networkmentioning
confidence: 99%